Percutaneous suprapubic tube bladder drainage after robot‐assisted radical prostatectomy: a step‐by‐step guide. (7th August 2013) - Ghani, Khurshid R.; Trinh, Quoc‐Dien; Sammon, Jesse D.; Jeong, Wooju; Simone, Andrea; Dabaja, Ali; Dusik, Stacey; Peabody, James O.; Menon, Mani
Abstract : Objective: To describe our technique of maintaining bladder drainage after robot‐assisted radical prostatectomy (RARP) using a percutaneous suprapubic tube (PST) in place of a urethral catheter. Methods: A watertight anastomosis permits placement of the PST. Contraindications include morbid obesity, concomitant inguinal hernia mesh repair, anticoagulation therapy, limited hand dexterity in the patient, bladder neck reconstruction and extensive adhesiolysis at RARP. The necessary equipment includes a 14‐F PST balloon catheter set, a three‐way connector, a connecting tube, a suture passer, 1/0 polypropylene sutures on a CT1 needle, a sterile plastic button, adhesive and steri‐strips. Results: The important steps for PST placement are: Step 1: robot‐assisted placement of a bladder wall anchor suture; Step 2: transferring the bladder wall suture to anterior abdominal skin; Step 3: guided placement of the PST under robotic vision; Step 4: securing the PST within the bladder and abdominal wall; Step 5. postoperative care: clamping the PST on postoperative day 5, recording each void and post‐void residual urine volumes in a patient diary, removal of the PST on postoperative day 7 after 48 h of voiding with residual urine <100 mL per void. Conclusion: We provide a concise step‐by‐step guide for placement of a PST during RARP as well as important management aspects for the successful adoption of this technique.